2013
DOI: 10.1158/0008-5472.can-12-2838
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial Flow in a 3D Microenvironment Increases Glioma Invasion by a CXCR4-Dependent Mechanism

Abstract: Brain tumor invasion leads to recurrence and resistance to treatment. Glioma cells invade in distinct patterns, possibly determined by microenvironmental cues including chemokines, structural heterogeneity, and fluid flow. We hypothesized that flow originating from pressure differentials between the brain and tumor is active in glioma invasion. Using in vitro models, we show that interstitial flow promotes cell invasion in multiple glioma cell lines. Flow effects were CXCR4-dependent, because they were abrogat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
201
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 159 publications
(217 citation statements)
references
References 47 publications
6
201
0
Order By: Relevance
“…However, these differences may reside in inherent differences of the chick CAM model and the rat model, different modes of migration of the analyzed tumor cells, or in the different application forms of the drug. The RT2 cell line, which was used in the astrocytoma study, has been shown to migrate mainly amoeboid-like (MMP-independent) in vitro (23). This is the same migratory mode as observed in BL2B95 cells.…”
Section: Discussionsupporting
confidence: 52%
“…However, these differences may reside in inherent differences of the chick CAM model and the rat model, different modes of migration of the analyzed tumor cells, or in the different application forms of the drug. The RT2 cell line, which was used in the astrocytoma study, has been shown to migrate mainly amoeboid-like (MMP-independent) in vitro (23). This is the same migratory mode as observed in BL2B95 cells.…”
Section: Discussionsupporting
confidence: 52%
“…Increased fluid pressure causes tissue compression, which leads to increased migration and transcriptional changes in cancer cells (Butcher et al, 2009). Elevated shear forces have been shown to induce GBM migration, in the direction of fluid flow, through mechanical activation of chemokine receptors (Munson et al, 2013). Changes in fluid pressure and flow are difficult to study in vivo and have thus been overlooked in glioma research.…”
Section: Effects Of Mechanical Changes On Glioma Progressionmentioning
confidence: 99%
“…Indeed, recent studies have shown that interstitial fluid flow alone can drive CCR7-dependent chemotaxis in CCL21 þ tumor cells, and that this autocrine gradient synergizes with the steep local paracrine gradient from a CCL21 þ lymphatic vessel (34). This "autologous chemotaxis" can also occur with other chemokine-receptor autocrine loops, for example as shown in CXCR4-dependent flow-driven invasion of glioma cells, which also express its ligand CXCL12 (35). This is yet another way in which lymphatic vessels in the tumor microenvironment can facilitate tumor cell metastasis, i.e., by virtue of the interstitial flow that they create by their drainage function, always directed toward and into the vessel.…”
Section: Lymphatic Transport Of Cellsmentioning
confidence: 99%